2011
DOI: 10.1074/jbc.m110.192450
|View full text |Cite
|
Sign up to set email alerts
|

Vav Family Rho Guanine Nucleotide Exchange Factors Regulate CD36-mediated Macrophage Foam Cell Formation

Abstract: Lipid-laden macrophages or "foam cells" are the primary components of the fatty streak, the earliest atherosclerotic lesion. Although Vav family guanine nucleotide exchange factors impact processes highly relevant to atherogenesis and are involved in pathways common to scavenger receptor CD36 signaling, their role in CD36-dependent macrophage foam cell formation remains unknown. The goal of the present study was to determine the contribution of Vav proteins to CD36-dependent foam cell formation and to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
39
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 33 publications
4
39
0
Order By: Relevance
“…However, the precise molecular mechanisms required for oxLDL uptake and macrophage foam cell formation are not fully understood. Notably, our newly published data revealed that CD36 contributes to activation of Vav family proteins in aortas from hyperlipidemic apoe null mice (7) and that oxLDL induces activation of macrophage Vav in vitro in a CD36 and Src family kinase-dependent manner (7). We also found that CD36-dependent uptake of oxLDL and foam cell formation was significantly reduced in macrophages deficient of Vav proteins (7).…”
supporting
confidence: 49%
See 2 more Smart Citations
“…However, the precise molecular mechanisms required for oxLDL uptake and macrophage foam cell formation are not fully understood. Notably, our newly published data revealed that CD36 contributes to activation of Vav family proteins in aortas from hyperlipidemic apoe null mice (7) and that oxLDL induces activation of macrophage Vav in vitro in a CD36 and Src family kinase-dependent manner (7). We also found that CD36-dependent uptake of oxLDL and foam cell formation was significantly reduced in macrophages deficient of Vav proteins (7).…”
supporting
confidence: 49%
“…Perhaps most significant is the critical role identified for dynamin 2, a Vav-interacting large molecular weight GTPase. Published studies have shown that Vavs regulate ligand-receptor endocytosis in other cell types (8,21,22), and indeed, we showed that vav-deficient macrophages had impaired maturation of oxLDL-containing endocytic vesicles and thus impaired ability to form foam cells (7). Dynamins are known to function in the fission of endocytic vesicles from the plasma membrane (28) and we found that dynamin-2 co-localized with oxLDLcontaining vesicles during CD36-mediated endocytosis of oxLDL (Fig.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Surprisingly, the level of 8-iso-PG-F2α did not decrease, so the pro-oxidant signals are triggered by the PMV-CD36 complex but not JNK. In macrophages, CD36 activates src-family kinases, Vav family guanine nucleotide exchange factors and MAPKs (23,24). Whether the other two kinases mediated this signal pathway remains to be determined; it is the limitation of our study.…”
Section: P L a T E L E T -D E R I V E D M I C R O V E S I C L E S P Rmentioning
confidence: 70%
“…Why this would be the case is not clear since PKG, activated by NO, actually promotes VSMC proliferation and PKG deficiency led to smaller lesions with fewer VSMC in hyperlipidemic mice (1972). Perhaps prolonged rapid flow stimulates changes in VSMC that are analogous to the normal compensatory vessel enlargement in areas of rapid flow, particularly during embryogenesis, but in the context of an advanced atherosclerotic plaque such changes may lead to paradoxical weakening of the fibrous plaque just under the area of endothelium exposed to the highest flow rates (1641,1642 (1449). Active PKC and Rac1 promote assembly and activation of NOX2 to enhance ROS production (1210).…”
Section: Newer Insights Into the Role Of Vsmc In Atherosclerosismentioning
confidence: 99%